Everything has an end, only the sausage has two : profit & purpose : the case of Rügenwalder Mühle - Schäfer, Carolin Andrea (2020)
Our society is increasingly confronted with the challenges of climate change and a growing world population. As a result, people are adapting their consumption behaviour and demand more sustainable products. A growing number of businesses respond to those changes by stimulating a transformational process to drive positive social change (Stephan et al., 2016). Companies are eager to adopt corporate social responsibility (CSR) measures to demonstrate initiative. Some even go beyond that by transforming into a mission-driven for-profit company – a form of hybridization. Rügenwalder Mühle (RM), a Germany-based sausage producer, successfully underwent such a transformation. From 2014 onwards, it revamped its business model by expanding its assortment with plant-based products. RM considers meat substitutes beneficial for the environment as it is more resource-saving and prevents high CO2-emissions. The case study showcases how the hybridization was initiated due to changing stakeholder perceptions; how the company dealt with consumer tensions during the process using the communicational tool of strategic ambiguity; and how future decisions can be evaluated according to a market orientation approach. The dissertation provides insights into hybridization success factors: First, it is important to carefully keep track of changing stakeholders and, based on that, draw the right innovative conclusions. Second, companies can manage their stakeholders during the hybridization process by embracing the diversity, rather than ignoring it. And third, an appropriate evaluation of strategies can help to gauge future decisions.